2018
DOI: 10.1021/acssuschemeng.7b03837
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Fast Pyrolysis of Biomass over Microporous and Hierarchical Zeolites: Characterization of Heavy Products

Abstract: Ultra-high resolution mass spectrometry combining various ion sources demonstrates the effects of hierarchical zeolite on the heavy molecular composition of bio-oil generated by fast-pyrolysis of lignocellulosic biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…The amount of oxygen in the final products is consequently higher than what is observed with “normal cigarettes” and favors the formation of oxygenated MSS compounds. As the composition of the biomass content of the cigarette is different, the investigation of MSS by LDI and ESI FTICR‐MS in negative detection mode may give relevant information as we demonstrated on the study of bio‐oil generated from biomass pyrolysis . The investigation of Indonesian and Kretek MSS by (−) LDI gives additional insights into the contribution of cloves to the final products observed in the MSS particle phases.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The amount of oxygen in the final products is consequently higher than what is observed with “normal cigarettes” and favors the formation of oxygenated MSS compounds. As the composition of the biomass content of the cigarette is different, the investigation of MSS by LDI and ESI FTICR‐MS in negative detection mode may give relevant information as we demonstrated on the study of bio‐oil generated from biomass pyrolysis . The investigation of Indonesian and Kretek MSS by (−) LDI gives additional insights into the contribution of cloves to the final products observed in the MSS particle phases.…”
Section: Resultsmentioning
confidence: 94%
“…Compounds with up to eight oxygen atoms are observed and the center of the Gaussian distribution is shifted to O5–O6 species. Such C x H y O w distributions have still been evidenced in the study of bio‐oil produced by pyrolysis of lignin or biomass and are relevant to the thermal degradation of the lignin, cellulose and hemicellulose of the biomass . The C x H y O w species observed in the study of Kretek MSS correspond to the superposition of the pyrolysis products of tobacco (O2 to O5), which typically contains 10% of cellulose, 12.5% of sugars and 3.5% of lignin and the pyrolysis of the cloves (O4 to O8), which is a ligno‐cellulosic material and contains close to 60% of cellulose and sugar .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Textural properties are often optimized by using nano-sized particles and introducing mesoporous structure to increase specific surface area and enhance reactant diffusion [16,18,19]. For example, hierarchical zeolites (HZ) have been widely used recently [20,21]. Due to the intercrystalline mesopores in bulk particles and large openings on the particle surface, the diffusion performance is optimized.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent type of zeolitic catalysts, the so-called hierarchical zeolites, which exhibit both the improved diffusion properties of mesoporous materials and the strong acidity and stability of zeolites [72][73][74], has also been investigated in biomass CFP [75][76][77][78][79][80][81]. However, few studies have been reported so far on lignin CFP.…”
Section: Introductionmentioning
confidence: 99%